TESLA SWITCH OF 4 BATTERIES BASED ON THE ARDUINO UNO BOARD - Polishchuk, Mykola; Grinyuk, Serhii; Kostiuchko, Serhii; Tkachuk, Anatolii; Savaryn, Pavlo (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2023)
The paper considered the theoretical information of generators for several power sources, schematic their solutions, and the main disadvantages and advantages. A generator for 4 batteries based on field-effect transistors with optical galvanic isolation and a clock generator built on the basis of the Atmega328 microcontroller, which is part of the Arduino Uno device, was studied. The result of the study was the confirmation of the existence of the "Tesla-switch" effect. A program code was developed for the alternate switching of six transistor switches of the optical decoupling. The structural diagram of the device was studied, and the influence of the generator frequency and the consumed power of the load on the output parameters of the device were determined. The considered idea of energy saving and environmental friendliness of power supply systems is relevant, in particular in cases of blackouts.